INTERAKSI SOSIAL PETANI SEBAGAI DAMPAK ALIH FUNGSI LAHAN DI KELURAHAN TAMANGAPA KOTA MAKASSAR - Sakmawati, Sakmawati; Firmansyah, Agung (Universitas Negeri Makassar, 2025)
The conversion of agricultural land to non-agricultural use that occurs in Tamangapa Village, Makassar City, can have a significant impact on the social life of farmers. When agricultural land that was previously used for food production or other agricultural activities is transformed into land for housing, industry, or infrastructure, farmers will experience major changes in their lives, both in the context of social interactions among farmers and with the broader community. This research is classified as qualitative research that employs observation, interviews, and documentation techniques for data collection. The research findings indicate that the social life of farmers in Tamangapa Village has changed, particularly regarding social interactions among farmers, following the conversion of agricultural land to non-agricultural use. The existing farmer groups continue to collaborate to find ways to ensure that agricultural activities can still be optimally conducted by utilizing the available agricultural land. In contrast, the interactions among the community as agricultural laborers have become strained. This is due to the fact that the community, as agricultural laborers, has lost their jobs, or in other words, the services of agricultural laborers are no longer required because of the availability of technology or machinery used by landowners or cultivators to harvest their agricultural products.